(untitled) (Research, Society and Development, 2020)
Hemangiomas are benign lesions of common vascular origin in the head and neck region, but rarely arise in the oral cavity. The management and knowledge of the diagnostic techniques are fundamental for the differential diagnosis. Monoethanolamine oleate, as a sclerosing agent, promotes an inflammatory reaction leading to endothelial fibrosis, being effective in the treatment of benign vascular lesions of the oral cavity; besides the adverse reactions are of low intensity and little reported in the literature; showing an alternative to surgical treatment. The purpose of this study was to report a series of cases of patients undergoing sclerotherapy and to discuss the results of treatment of benign oral vascular lesions with monoethanolamine oleate. Four patients seen at the Bucomaxillofacial Surgery and Traumatology servisse of the Oswaldo Cruz University Hospital (CTBMF / HUOC / UPE) – Recife/PE with oral lesion complaint. After detailed clinical examination and the use of vitro pressure, hemangiomas diagnoses were obtained opting for treatment based on sclerotherapy with monoethanolamine oleate presenting satisfactory clinical resolution. In the cases reported here, the sclerosing agent has proved to be effective for the treatment of hemangiomas in the oral cavity.